Evaluation of the costeffectiveness of sterile insect release strategies against painted apple moth Teia anartoides - Wee, S.L.; Kean, J.M.; Stephens, A.E.A.; Suckling, D.M. (New Zealand Plant Protection, 2006)
Although the painted apple moth (PAM) eradication programme in West Auckland appears to have been successful the large volume of trade from Australia PAMs native range makes reinvasion likely Recent work has focused on modelling the spatial and temporal effects of optimal release strategies in the sterile insect technique (SIT) programme to enable assessment of the time required and likelihood of eradication success However the costeffectiveness of each strategy is not known Based on the rearing and operational costs from the past PAM SIT release programme the unit cost of a single irradiated male moth for a release programme has been quantified A simple economic model for cost analyses and comparison of a few selected SIT release strategies at ge;95 confidence level of eradication success is presented This model could be used to select an appropriate costeffective strategy thus aiding in prompt decisionmaking of PAM reincursion responses